Способы представления дифференциальных амплитудных спектров импульсов частичных разрядов в твердой изоляции - Беспрозванных, Анна Викторовна (Інститут електродинаміки НАН України, 2011)
Geometrical parameters and number of air inclusions in solid insulation are defined on the basis of the decision of equation Volterra only in case of monotonous change of differential peak spectra (ȾPS) of pulses of partial dischargers. Otherwise the average parameters of air inclusions are defined. The estimation of quality of solid insulation is carried out by representation of set DPS in double logarithmic scale. Comparison of curves DPS is carried out on width of a strip of spectra of partial dischargers without mathematical processing.
Способи зображення диференційних амплітудних спектрів імпульсів часткових розрядів у твердій ізоляції
Ways of representation of differential peak spectra of pulses of partial disharges in solid insulation
Keywords: частичные розряди; твердая изоляция; дифференциальные амплытудные спектры; часткові розряди; тверда ізоляція; дифференціальні амплітудні спектри; partial dischargers; solid snsulation